Assédio moral como acidente de trabalho no meio ambiente laboral - BARROS, Nilson José Gomes (Universidade Federal do Pará, 2017)
Bullying is a topic that is part of the study field of labor law by interfering in labor relations and affect the performance of worker rights. This paper sets clear and indicate alternatives that can contribute to a new interpretation of the rules punitive labor law, starting with a new look, a new vision, based on a proposal for improving the quality of life of the worker. We carried out an explanation in the first chapter, where we discuss bullying at work, highlighting the history of workers in Brazil, as well as the concept and characteristics of bullying at work, causation and evidence of bullying, dealing with this aspect of reversal of the burden of proof in harassment. We focus on bullying as illegal labor and how the issue is being addressed in Brazilian legislation. Introducing the possibility of joining with state regressive action against companies that practice bullying, and at the end of the chapter we will approach the organizational bullying. The second chapter will deal with aspects of the accident at work, showing its concept and its features, showing its consequences as aid-accident stability of accident, making explanations on liability for accidents at work and the issue of compensation for moral damage due to accident at work, at this point discuss the technical link epidemiological and necessity issued by the cat (on accident), making the analogy of the concepts of accidents at work and bullying. In the third chapter, we highlight several aspects of the work environment which is inserted into the natural environment and ecosystems, according to the Constitution of 1988, casts wide legislation that protects the environment of work, we consider also the guiding principles of the Law work, highlighting the protection, equality and freedom, demonstrating the need to promote human dignity that underlies the Constitution of 1988. In the fourth chapter, we show our thesis, that bullying is a kind of accident at work, in order that the conceptual similarities in that both cause injury to employees arising from employment relationship, and both have the same need , that causation of injury, will be reflected in the employment relationship. At this point, we will make a hermeneutic approach, in which scientific concepts are exposed on depression and burnout syndrome as occupational disease, arising from bullying. In the last chapter, we present some measures to prevent bullying at work, including the trade union actions, state, highlighting the important role of the Ministry of Labor, as well as some preventive measures that companies can take to prevent bullying taking in order that its consequences are disastrous for workers and for organizations. The methodology involved literature search, consulting on Internet sites and bills. We conclude that we need laws that are tough on combating and prevention of situations of bullying, as well as the reworking of management plans developed by planning agencies for the rehabilitation of organizations seeking to promote quality improvements in social relations at work are actions that believe will help to decrease the likelihood of bullying.